1923 Vt. Acts and Resolves 127, No. 130, § 1 - (:unkn) unknown (My University, 1923)
Prohibited using, carrying, or possessing a machine gun or automatic rifle while hunting.
Keywords: HUNTING REGULATION; MACHINE GUN RESTRICTION